No need for an intention to deceive? Challenging the traditional definition of lying. (19th May 2017) - Rutschmann, Ronja; Wiegmann, Alex
Abstract: According to the traditional definition of lying, somebody lies if he or she makes a believed-false statement with the intention to deceive. The traditional definition has recently been challenged by non-deceptionists who use bald-faced lies to underpin their view that the intention to deceive is no necessary condition for lying. We conducted two experiments to test whether their assertions are true. First, we presented one of five scenarios that consisted of three different kinds of lies (consistent bald-faced lies, conflicting bald-faced lies, and indifferent lies). Then we asked participants to judge whether the scenario at hand was a lie, whether the speaker intended to deceive somebody, and how they would judge the behavior in terms of morality. As expected, our results indicate that the intention to deceive is not a necessary condition for lying. Participants rated indifferent lies to be lies and judged that no intention to deceive was involved in these cases. In addition, all bald-faced lies were evaluated as lies. However, participants widely ascribed an intention to deceive to bald-faced lies, which thus might not apply as counterexamples against the traditional definition of lying. Besides, lies are judged as morally wrong regardless of an intention to deceive .